Short-term results of laparoscopic and open complete mesocolic excision with D3 lymph node dissection for left-sided colon cancer - P. V. Tsarkov; I. A. Tulina; A. Yu. Kravchenko; A. V. Leont’Yev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate possible advantages and shortcomings of laparoscopic complete mesocolic excision with D3 lymph node dissection in the treatment of left-sided colon cancer in comparison to open approach according to analysis of short-term outcomes. Material and methods. Investigation was designed as retrospective-prospective case-control study (with analog group comparison). Patients with left-sided colon cancer of stages II-III were selected from prospectively collected database. Groups have been generated according to case-control principle: the I group included patients who underwent open complete mesocolic excision with D3 lymph node dissection, the II group comprised patients who underwent laparoscopic intervention in the same volume. Results. Each group included 54 patients. Duration of operation and volume of intraoperative blood loss in the II group patients was less, than in the I group. Postoperative morbidity rate had no statistically significant differences in both groups. Rehabilitation in early postoperative period was faster in the II group vs I group. Conclusion. Laparoscopic complete mesocolic excision with D3 lymph node dissection is safe type of surgery, which allows to improve short-term results of surgical treatment of patients with stage II-III left-sided colon cancer. Morphological scores indicate identical efficacy in achievement of radical treatment for laparoscopic and open techniques from the standpoint of modern oncology principles. However, correct estimation of long-term outcomes require further studies.